Bacterial Dynamics in Supraglacial Habitats of the Greenland Ice Sheet - Nicholes, Miranda Jane; Williamson, Christopher James; Tranter, Martyn; Holland, Alexandra; Poniecka, Ewa; Yallop, Marian Louise; , The Black & Bloom Group; Anesio, Alexandre; Tranter, Martyn; Anesio, Alexandre; Yallop, Marian; Williamson, Christopher; et al. (Frontiers in Microbiology, 2019)
Current research into bacterial dynamics on the Greenland Ice Sheet (GrIS) is biased towards cryoconite holes, despite this habitat covering less than 8 % of the ablation (melt) zone surface. In contrast the expansive surface ice, which supports wide-spread Streptophyte micro-algal blooms thought to enhance surface melt, has been relatively neglected. This study aims to understand variability in bacterial abundance and production across an ablation season on the GrIS, in relation to micro-algal bloom dynamics. Bacterial abundance reached 3.3 ± 0.3 x 105 cells mL-1 in surface ice and was significantly linearly related to algal abundances during the middle and late ablation periods (R2 = 0.62, p < 0.05; R2 = 0.78, p < 0.001). Bacterial production (BP) of 0.03 – 0.6 g C L-1 h-1 was observed in surface ice and increased in concert with glacier algal abundances, indicating that heterotrophic bacteria consume algal-derived dissolved organic carbon. However, BP remained at least 28 times lower than net primary production, indicating inefficient carbon cycling by heterotrophic bacteria and net accumulation of carbon in surface ice throughout the ablation season. Across the supraglacial environment, cryoconite sediment BP was at least four times greater than surface ice, confirming that cryoconite holes are the true ‘hot spots’ of heterotrophic bacterial activity.